2008
DOI: 10.1253/circj.72.1270
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Intravascular Ultrasound Findings in 1,009 Coronary Artery Disease Patients

Abstract: Background The aim of this study was to assess the age-related differences in intravascular ultrasound (IVUS) findings of target lesions in patients with coronary artery disease. (n=93)]. Calcified plaque (18%, 25%, 33%, 38%, and 46%, p<0.001) and negative remodeling (29%, 48%, 44%, 44%, and 66%, p<0.001) were most common, and reference segment plaque burden (35±11%, 35±10%, 39±10%, 38±10%, and 40±11%, p<0.001) was greatest in Group V. Plaque rupture (52%, 31%, 42%, 38%, and 20%, p=0.009) and thrombus (38%, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
3
17
1
1
Order By: Relevance
“…and diffuse atherosclerosis, whereas younger patients have a more unstable coronary plaque morphology. 25 The higher degree of coronary calcification in the elderly is in line with the age-related increase in inactive dp-ucMGP. In morphological studies, coronary plaque calcification was not associated with instability, whereas ruptured plaques showed little calcification.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…and diffuse atherosclerosis, whereas younger patients have a more unstable coronary plaque morphology. 25 The higher degree of coronary calcification in the elderly is in line with the age-related increase in inactive dp-ucMGP. In morphological studies, coronary plaque calcification was not associated with instability, whereas ruptured plaques showed little calcification.…”
Section: Discussionmentioning
confidence: 79%
“…26 Furthermore, the number of coronary arterial segments with noncalcified plaque as assessed by computed tomography was associated with a 30% 27 to 71% 28 higher incidence of coronary 27 or cardiac 28 events in patients with suspected 27,28 or known 28 coronary artery disease. In view of the currently available literature, we assume that inhibition of plaque calcification by active MGP is a risk factor in the coronary circulation, [25][26][27][28] whereas in large conduit arteries, such as the femoral artery, 4 the opposite is the case. An alternative explanation for the inverse association between coronary events and dp-ucMGP levels might reside in the vitamin K-dependent activation of growth arrest-specific protein 6 (Gas6).…”
Section: Discussionmentioning
confidence: 99%
“…Both histological [30][31][32] and IVUS studies [33,34] have established that the burden of coronary plaque increases with age, and that the extent of calcification also increases with age. In comparison to IVUS, CCTA is a safer, non-invasive technique that likewise allows for both an estimation of luminal stenosis and plaque composition.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] Here we showed that aging is associated with the reduction of activity of only one of the various antioxidant enzymes. In addition, we investigated the association of aging with the tolerance of macrophages against oxLDL.…”
Section: Mnsod Activity and Macrophage Apoptosismentioning
confidence: 94%